Food inspection using high performance quantum cascade laser - He, Yuzhi (Nanyang Technological University, 2022)
Food inspection techniques are essential to address food safety issues. In this paper, based on a more systematic review of commonly used food inspection techniques, a special study on edible oil safety testing techniques is conducted. Through an extensive review of the literature, the author concluded that the late start of mid-infrared spectroscopy has strong advantages for food safety testing. According to the actual situation, edible oil is used as the experimental samples in this dissertation. The experimental equipment includes FTIR (Fourier Transform infrared spectroscopy), QCL (Quantum Cascade Laser), DAQ (Data Acquisition) and Lock-in amplifier. FTIR measures the complete spectrum of edible oil; QCL measures the characteristic absorption peaks in part of the spectrum of edible oil; DAQ can be used to acquire data. The Lock-in amplifier can extract weak signals from the noise and measure them accurately. The purpose of the experiments was to measure the spectra of different edible oils and then compare their absorption peaks as well as bandgap to determine their difference. In the experiment, the author first measured the olive oil and sun flower oil using FTIR, and selected the absorption peak (960-1300cm-1) from the spectrogram that is suitable for further measurement using QCL.The QCL experiment part includes two steps, one is to obtain the appropriate oil film thickness to ensure the spectrogram effect, and the other is to obtain the absorption peaks of various edible oils as well as bandgap for comparative analysis to determine the differences of the oils. The authors believe that the appropriate oil film thickness is very important for the measurement to obtain the spectrogram of the ideal absorption peak. If the oil film is too thick, the laser penetration is not enough to pass through; if the oil film is too thin, the spectrogram will show interference phenomenon, so the first step is to obtain the appropriate oil film thickness by adding spacer. After determining the film thickness, the absorption peak spectra of five kinds of edible oils, olive oil, canola oil, soya bean oil, sun flower oil, peanut oil were obtained by one set of experiments, and the absorption peak spectra of different brands of canola oil were obtained by another set of experiments. After the normalization of the above two groups of experimental results, it is obvious that the general trend of their absorption peaks is very similar. Finally, the bandgap at transparency 0.5 was used to compare each edible oil in detail to determine the differences between the edible oils. The experimental results of this thesis validate the feasibility of using mid-infrared spectroscopy to test edible oil, and are promising to be extended to other food samples for food inspection.